Developing feasible healthy diets for Ethiopian women of reproductive age: A linear goal programming approach - Bekele, Tesfaye Hailu; Rooijen, Maike van; Gerdessen, Johanna C.; Brouwer, Inge D.; Feskens, Edith J.; Trijsburg, Laura; Alemayehu, Dawit; Vries, Jeanne H.M. de (Cambridge University Press, 2023)
Objective: To develop a healthy diet for Ethiopian women closely resembling their current diet and taking fasting periods into account while tracking the cost difference.